2019
DOI: 10.1038/s41598-019-39182-6
|View full text |Cite
|
Sign up to set email alerts
|

Differential epithelial and stromal protein profiles in cone and non-cone regions of keratoconus corneas

Abstract: Keratoconus (KC) is an ectatic corneal disease characterized by progressive thinning and irregular astigmatism, and a leading indication for corneal transplantation. KC-associated changes have been demonstrated for the entire cornea, but the pathological thinning and mechanical weakening is usually localized. We performed quantitative proteomics using Sequential Windowed Acquisition of All Theoretical Fragment Ion Mass Spectrometry (SWATH-MS) to analyze epithelial and stromal changes between the topographicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 73 publications
1
28
0
Order By: Relevance
“…The SWATH-MS technology is emerging as a preferred tool for clinical proteomic studies with a large number of samples involved, especially when analyzing limited volume of samples for multiple time points [13] . Our group has previously used this method to document the tear protein changes in patients with thyroid eye diseases and keratoconus [17] , [18] . Our data showed that during the first month postoperatively, the complement activation and immunoglobulin production were the dominant responses shown in both SMILE and LASIK.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The SWATH-MS technology is emerging as a preferred tool for clinical proteomic studies with a large number of samples involved, especially when analyzing limited volume of samples for multiple time points [13] . Our group has previously used this method to document the tear protein changes in patients with thyroid eye diseases and keratoconus [17] , [18] . Our data showed that during the first month postoperatively, the complement activation and immunoglobulin production were the dominant responses shown in both SMILE and LASIK.…”
Section: Discussionmentioning
confidence: 99%
“…Tear proteins from finely cut Schirmer’s strip were extracted by ammonium bicarbonate (50 mM, 100 μl per strip; Sigma-Aldrich, St. Louis, MO, USA) at 1300 rpm, room temperature (23 °C) for 1 h, and the protein concentration was measured. Protein samples (100 μg) were applied for SWATH-MS and a spectral library was established as previously described [17] , [18] . The digested samples were reconstituted in loading buffer (0.1% formic acid, 2% acetonitrile in water), and iRT standard (Biognosys, Switzerland) was spiked.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In primary keratoconus, changes in the expression of corneal epithelium and stroma-specific genes at the apex of the cone result in focal weakening in keratoconus [ 16 ]. Also, changes in keratoconus-related proteome occur in the noncone regions of keratoconus corneas [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Keratoconic eyes are less resistant to deformation in post-LASIK ectasia due to focal weakening and significant reduction in corneal stiffness. This phenomenon results from variations in the expression of corneal epithelium and stroma-specific genes at the apex of the cone as well as changes in keratoconus-related proteome in non-cone regions of keratoconus corneas [ 9 11 ]. Accordingly, detecting keratoconus among refractive surgery candidates is crucial since removing tissue from an inherently weak cornea further weakens and threatens its integrity [ 12 ].…”
Section: Introductionmentioning
confidence: 99%